ANALISIS STRATEGI PEMASARAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) SALON AURA DEPOK DALAM MENGHADAPI ERA NEW NORMAL PANDEMI COVID-19. - Safaza Azizah (2022)
Micro, Small and Medium Enterprises play a very important role in the Indonesian economy. However, the pandemic has reduced MSME turnover in various parts of Indonesia, including the city of Depok, West Java. This study aims to identify and analyze the marketing strategy of MSME Salon Aura Depok in facing the new normal era of the COVID-19 pandemic by using the marketing mix 7Ps and SWOT analysis. Using qualitative research methods with primary data obtained directly from sources, then validated using data triangulation techniques and then analyzed using the Miles and Huberman method. The results of the research based on SWOT by considering the 7P elements produce an SO strategy, namely (1) product, improving product quality and increasing product/service variety, (2) price, always updating and adjusting the standard price of the beauty salon market, (3) place, always studying competitors to be able to outperform and improve the quality of services, (4) promotion, expand networks social media, advertise more often, and provide gifts/souvenirs with certain conditions, (5) people, always provide training continuous to employees, (6) process, by making and clarifying SOPs and written job descriptions at salons, and (7) physical evidence, periodically repainting wall paints, upgrading furnishings, and always checking and maintaining goods, tools, and facilities provided.